Correlation Between Anti-Myelin Proteolipid Protein (PLP) Antibodies and Disease Severity in Multiple Sclerosis Patients With PLP Response-Permissive HLA Types - Greer, Judith M.; Trifilieff, Elisabeth; Pender, Michael P. (Frontiers in Immunology, 2020)
The most prominent pathological features of multiple sclerosis (MS) are demyelination and neurodegeneration. The exact pathogenesis of MS is unknown, but it is generally regarded as a T cell-mediated autoimmune disease. Increasing evidence, however, suggests that other components of the immune system, particularly B cells and antibodies, contribute to the cumulative CNS damage and worsening disability that characterize the disease course in many patients. We have previously described strongly elevated T cell reactivity to an extracellular domain of the most abundant CNS myelin protein, myelin proteolipid protein (PLP) in people with MS. The current paper addresses the question of whether this region of PLP is also a target of autoantibodies in MS. Here we show that serum levels of isotype-switched anti-PLP181-230 specific antibodies are significantly elevated in patients with MS compared to healthy individuals and patients with other neurological diseases. These anti-PLP181-230 antibodies can also live-label PLP-transfected cells, confirming that they can recognize native PLP expressed at the cell surface. Importantly, the antibodies are only elevated in patients who carry HLA molecules that allow strong T cell responses to PLP. In that subgroup of patients, there is a positive correlation between the levels of anti-PLP181-230 antibodies and the severity of MS. These results demonstrate that anti-PLP antibodies have potentially important roles to play in the pathogenesis of MS.